CULTURAL AND LEGAL FACTORS OF OPTIMIZATION OF THE IDEOLOGY OF STATE-BUILDING IN UKRAINE - O. V. Krasnokutskyi (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The Purpose is to investigate the legal cultural phenomenon in the riches of the contours of its essence, raising the level of this phenomenon as part of the system of determinants of the optimization of ideology of state-building in modern Ukraine. Methodology. The study is based on the principles of materialist dialectics and the principles of historicism, social determinism, complexity. The scientific novelty. The cultural and legal factors of optimization of the ideology of state-building are conceptually considered for the first time in modern Ukraine; three methodological points that should be targeted in the definition of «legal culture» are outlined; the definition of legal culture is improved; a working template program of improvement and increase of the level of legal culture in contemporary Ukrainian society is developed; four key conceptual areas of the program are outlined. Conclusions. Legal culture can be defined as a separate category to mark the legal system which was historically formed and the institutions of a state-organized society that are correlated with it, and also the legal knowledge and motives, forms, techniques and methods of legal activities, values, estimates with the necessity inherent to every people, class, nation, community groups, to the individual person at a certain stage of their development. Rise of the level of legal awareness is one of the leading systematic factors, cultural and code keys to optimizing the development of state-building ideology in the conditions of today's Ukraine. The program for the improvement and enhancement of legal culture in contemporary Ukrainian society is composed of four major conceptual areas: the growth of basic legal literacy; the rise of their legal awareness; the increase of theoretical justification of the existing legal reality, the prospects for its future development, the increase of the efficiency of the legal theory; progressive formation of legal ideology.